Ethnobotanical Study of Wild Plant Species Used by Local People of Bhageshwor Rural Municipality, Dadeldhura, Nepal - Chataut, Gajendra Prasad (Api Journal of Science, 2025)
Ethnobotany is a science that integrates society and plants, contributing to biodiversity conservation strategy of a country. The study aims to document the ethnobotanical knowledge of wild plant species in Bhageshwor Rural Municipality, Dadeldhura. This study was conducted from October 2023 to October 2024 for data collection through interviews, group discussions with key informants or local knowledgeable individuals (N=200), and semi-structured and open-ended questionnaires, as well as field visits to adjoining villages, using participatory observations. A total of 70 wild plant species with 65 genera and 40 families are recorded, among them 65 species are native while remaining five are invasive alien species. Local people use 28 species (40%) for food and fodder and only two species were used as timber. The ethnobotanical study of wild plant species shows the cultural, heritage and social values of respective plants. So, large number of research works may be helpful for the exploration and conservation of wild plant species; therefore, local governments should manage and document the local wild plant species through ethnobotany.